2003
DOI: 10.1073/pnas.0931291100
|View full text |Cite
|
Sign up to set email alerts
|

The nature of heme/iron-induced protein tyrosine nitration

Abstract: Recently, substantial evidence has emerged that revealed a very close association between the formation of nitrotyrosine and the presence of activated granulocytes containing peroxidases, such as myeloperoxidase. Peroxidases share heme-containing homology and can use H 2O2 to oxidize substrates. Heme is a complex of iron with protoporphyrin IX, and the iron-containing structure of heme has been shown to be an oxidant in several model systems where the prooxidant effects of free iron, heme, and hemoproteins may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 51 publications
6
133
1
1
Order By: Relevance
“…Alternatively, based on a previous report (41), it was tempting to consider that PMAboosted production of reactive oxygen species, associated with iron knocked out from an IRP-1-disrupted [Fe-S] cluster, would favor local nitration through Fenton chemistry. Indeed, in vitro studies previously showed that redox metals, particularly iron, can catalyze protein tyrosine nitration promoted by peroxynitrite (42) or by nitrite/H 2 O 2 (41,43). However, our results showing that myeloperoxidase inhibitors completely abrogated nitration strongly suggest that "autocatalytic" nitration of IRP-1 by its own iron was not relevant under these conditions.…”
Section: Endogenous Irp-1 Nitration In Activated Macrophagescontrasting
confidence: 53%
“…Alternatively, based on a previous report (41), it was tempting to consider that PMAboosted production of reactive oxygen species, associated with iron knocked out from an IRP-1-disrupted [Fe-S] cluster, would favor local nitration through Fenton chemistry. Indeed, in vitro studies previously showed that redox metals, particularly iron, can catalyze protein tyrosine nitration promoted by peroxynitrite (42) or by nitrite/H 2 O 2 (41,43). However, our results showing that myeloperoxidase inhibitors completely abrogated nitration strongly suggest that "autocatalytic" nitration of IRP-1 by its own iron was not relevant under these conditions.…”
Section: Endogenous Irp-1 Nitration In Activated Macrophagescontrasting
confidence: 53%
“…For example, nitroxyl, heme proteins, transition metals and/or peroxidases can catalyze NTYR formation. Intense NTYR staining in the blood bolus may, therefore, reflect heme iron catalysis of tyrosine nitration in an environment of Hb digestion and high · NO flux [42]. Kumar et al [39] hypothesized that · NO synthesis following parasite infection in An.…”
Section: Ntyr Formation In the A Stephensi Midgutmentioning
confidence: 99%
“…Elevations of redox active metals systems such as iron (Fe), copper (Cu), and manganese (Mn) contribute to oxidative damage in disease states (12,14). Also, inflammatory conditions trigger the release of leukocyte peroxidases, including myeloperoxidase (MPO) and eosinophil peroxidase (EPO), which play central roles in tissue oxidant formation (13,15,41 …”
Section: The Transition Metal-dependent Formation Of Strong Oxidants mentioning
confidence: 99%
“…However, the role of peroxynitrite as a central species in biological nitration has been more recently questioned (11,12), and alternative pathways, most notably mechanisms that depend on the formation of • NO 2 by the action of hemeperoxidases and͞or transition metal complexes on a main product of • NO metabolism, nitrite (NO 2 Ϫ ), have been presented as contributors (12)(13)(14)(15).…”
mentioning
confidence: 99%